Primary Closure or Delayed Primary Closure? Assessment of Optimum Management of Surgical Wounds for Perforated Appendicitis - Fuad, Muqdad; Modher, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Open appendectomy is the treatment of choice for perforated appendicitis. Perforated appendicitis is associated with a 15–20% risk of developing post-operative wound infection, which the later associated with increased morbidity as increasing post-operative pain, longer hospital stay, suppurative wounds, patient dissatisfaction and increase cost of treatment. Some literatures revealed inconsistent results related to the incidence of surgical site infection (SSI) between delayed primary closures (DPC) and primary closure (PC) in open appendectomy for perforated appendicitis. AIM: The objective of the study is to define the best practice of wound management in patients operated on for perforated appendicitis. PATIENTS AND METHODS: One hundred and twenty patients having perforated appendicitis underwent open appendectomy enrolled in the study. The patients were randomly grouped according to the method of managing the surgical incisions into two groups; patients with their incisions closed primarily (PC) and those with their incisions left open to be frequently dressed for 5 days with Betadine-soaked gauze packing till it become clean then closed (DPC). An infected wound was assigned as such if purulent discharge yielded from the incision site. Results to be addressed were the incidence of SSI and the hospitalization length. RESULTS: Out of the total 120 patients, 19.17 % developed SSI following closure of the incision. Patients managed by PC revealed higher rate of SSI than DPC group (32.8% vs. 5.1%, p < 0.001) and longer hospitalization (8.3 vs. 6.4 days, with a p < 5%). CONCLUSION: DPC is preferred policy over PC when managing an open appendicectomy wounds for perforated appendicitis, as the former is associated with low incidence of wound infection and shorter hospitalization.